PENGARUH DPK, NPL DAN ROA TERHADAP PENYALURAN KREDIT PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-20 - Asih Handayani (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2018)
The purpose of this research is to analyze the influence of Dana Pihak Ketida (DPK), Net Performing Loan (NPL), and Return on Asset (ROA) either simultaneously or partially to credit distribution at commercial banks listed in Indonesia stock exchange period 2011-2014. This research used regression analysis methode. The results indicates that simultaneously DPK, NPL, and ROA have a significant effect to credit distribution. Partially, DPK and ROA have positive and significant effect to credit distribution. While the variable of NPL have a significant negative effect to credit distribution.Keywords : DPK, NPL, ROA, credit distribution